The magnetic instability of Yb2Pd2(In,Sn) in a non-Fermi liquid environment - Bauer, E. (2005)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina